Phosphatidylcholines from Pieris brassicae eggs activate an immune response in Arabidopsis - Stahl, Elia; Brillatz, Théo; Ferreira Queiroz, Emerson; Marcourt, Laurence; Schmiesing, André; Hilfiker, Olivier; Riezman, Isabelle; Riezman, Howard; Wolfender, Jean-Luc; Reymond, Philippe (eLife, 2020)
Recognition of conserved microbial molecules activates immune responses in plants, a process termed pattern-triggered immunity (PTI). Similarly, insect eggs trigger defenses that impede egg development or attract predators, but information on the nature of egg-associated elicitors is scarce. We performed an unbiased bioactivity-guided fractionation of eggs of the butterfly Pieris brassicae . Nuclear magnetic resonance (NMR) spectroscopy and mass spectrometry of active fractions led to the identification of phosphatidylcholines (PCs). PCs are released from insect eggs, and they induce salicylic acid and H 2 O 2 accumulation, defense gene expression and cell death in Arabidopsis , all of which constitute a hallmark of PTI. Active PCs contain primarily C16 to C18-fatty acyl chains with various levels of desaturation, suggesting a relatively broad ligand specificity of cell-surface receptor(s). The finding of PCs as egg-associated molecular patterns (EAMPs) illustrates the acute ability of plants to detect conserved immunogenic patterns from their enemies, even from seemingly passive structures such as eggs.